A Holistic Model of English Lesson-Unit Assessment for Junior High School Students - Desi Rochmawati (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2015)
Assessment in the learning process is very important. It is useful to know whether the teaching and learning process succeed or not. It can help to identify the students‘ achievement. An assessment is usually done by teachers and it covers the three aspects; knowledge, skills, and attitude (social and spiritual). In accordance with curriculum 2013, this study develops the model of assessment which is simpler and integrated. Moreover, teachers right now have many things to do related with administration affairs and other portfolios. They do not want to be burdened with some kinds of evaluation or assessment forms which will take too much of their time. This study, therefore, is aimed at designing a holistic model of assessment, which is designed for the unit lesson. The model is a holistic assessment model. In the model, Core Competence 1 (CC1) and Core Competence 2 (CC2) are not indicated explicitly because they are integrated in Core Competence 3 (CC3) and Core Competence 4 (CC4). The data were collected by having group discussion and sharing a questionnaire to the students in English Language Studies. The result of this study is a holistic model of assessment to assess Junior High School students‘ achievement in learning English. This model of assessment is designed especially to assess students‘ achievement in every unit lesson. The model is presented in a table with likert scale scoring of 1 to 4. Some explanation is also needed in certain points. The assessment is conducted by the students, they do self-assessment and peer assessment. The teacher does portfolio assessment of the student‘s work. A Holistic Assessment for Junior High School is the appropriate form because in the model, a holistic approach has been implemented: the contents are not too complex but they already represent the whole competence.